Prototipe Alat Pengering Pakaian Berbasis Arduino Uno - Febrianto, Muhammad Mahrush; Akbar, Fikar Muhammad; Bintoro, Jusuf (Autocracy: Jurnal Otomasi, Kendali, dan Aplikasi Industri, 2017)
Unpredictabel weather exchange requires a technology development. The tipycally on drying system it brings some ideas to create a clothes dryer based Arduino UNO instead of conventional process by drying under the sun. The aim of this project is to designed and made a drying clothes equipment based on Arduino UNO. Arduino UNO was used as a controller in the drying process electronically. It was an easier way to dry the clothes without having to wait for good weather. SHT11 sensors was used to detect room temperature and humidity in the dryer, push button switches were used as switches to determine the limits of temperature and humidity. Halogen lamp that emits 500 watts of heat used as a component of the drier and extra fan was used to distribute heat in was drying room. This device will automatically control the drying process based on the temperature in the furnace room. Clothes drier will be heated to the upper limit temperature (high) that has been regulated and went down to the minimum temperature (low) so it went on and on until the clothes dried and then it would be turned off automatically. Perubahan cuaca yang tidak menentu menunutut adanya perkembangan teknologi, hal inilah yang memunculkan ide untuk menciptakan alat pengering pakaian berbasis Arduino UNO sebagai pengganti pengeringan secara konvensional yaitu dengan cara menjemur dibawah sinar matahari. Tujuan dari proyek ini adalah merancang dan membuat sebuah alat pengering pakaian berbasis Arduino UNO. Arduino UNO digunakan sebagai pengontrol dalam proses pengeringan secara elektronik. Hal ini lebih mudah untuk mengeringkan pakaian tanpa harus menunggu cuaca cerah.Sensor SHT11 digunakan sebagai pendeteksi suhu dan kelembaban ruangan dalam alat pengering. Lampu halogen 500 Watt yang mengeluarkan panas digunakan sebagai komponen pengering dan extra fan DC digunakan untuk menyebarkan panas dalam ruangan pengering. Alat ini akan mengontrol proses pengeringan secara otomatis berdasarkan suhu dalam ruang pemanas. Pengering pakaian dipanaskan sampai suhu batas atas (high) yang telah diatur dan turun sampai pada temperature minimum (low) begitu seterusnya sampai pakaian kering setelah pakaian kering alat pengering akan mati secara otomatis.